(untitled) (Plant Bulletin, 2025)
Solar drying is an important method of maintaining food security and food quality through safe process of lowering the level of moisture content in Horticultural products. Although it works, one of the major problems is to optimize the process to have the energy efficiency and quality of products. The literature in the past, on plum drying has tended to involve taking the thin-layer models that simplify the convective conditions based on the fact that the mass and heat transfer coefficients are constant. This paper fills this gap by creating a more realistic more physics-based model which combines detailed airflow dynamics with product drying kinetics of forced-air plum drying. In a Completely Randomized Design with three repetitions a whole plum were dried in a chamber that was attached to a flat-plate solar collector under three temperatures (45-65 °C) and three velocities of air (0.1-1.0 ms-1). The maximum moisture loss (2.629 % WB) and moisture diffusivity (1.76 x 10-9 ms-1) was highest at 65d °C and maximum activation energy (46.97 KJ.mol-1) was highest at this temperature. The best model to have explained the drying kinetics was the Modified Page model; (R2 = 0.99, RMSE = 0.08, χ² = 0.62). The findings clearly indicate that the most significant factor which had a statistically significant bearing on moisture removal was temperature, whereas air velocity did not have a significant influence. This proven model is a sound mechanism of optimizing the mechanics of the processes, which allows the development of more effective solar dryers that do not waste energy and at the same time, they are able to maintain the quality of the product.